You've Got Mail … and Need Follow‐up: The Effect and Patient Perception of E‐mail Follow‐up Reminders After Emergency Department Discharge. (24th December 2014) - Sharp, Brian; Singal, Bonita; Pulia, Michael; Fowler, Jennifer; Simmons, Stefanie; Gratton, Matthew
Abstract Objectives The hypothesis was that a reminder about recommended primary care physician (PCP) follow‐up, sent via e‐mail to patients discharged from the emergency department (ED), would increase the proportion of patients who followed up with their PCPs within the recommended time frame. Patient receptiveness to e‐mail follow‐up reminders was also assessed. Methods This was a mixed methods clinical intervention study with subjects randomized either to receive the usual care discharge instructions only or to also receive a reminder e‐mail message the day after the ED visit. The reminder e‐mail contained the subject's PCP's name and address and the recommended PCP follow‐up time interval. A blinded review of outpatient PCP medical records was conducted to determine whether and when follow‐up occurred. Researchers attempted to contact patients with a telephone survey 2 weeks after their ED visits. The primary outcomes between groups were compared using chi‐square tests and relative risks (RRs) with 95% confidence intervals (CIs). Results Thirty‐three percent of the intervention group and 32% of the control group followed‐up as recommended (RR = 1.04, 95% CI = 0.81 to 1.33); 52% of the intervention group and 48% of the control group followed‐up within 10 days of the recommended time (RR = 1.08, 95% CI = 0.91 to 1.29). The 334 patients (57%) successfully contacted via telephone demonstrated a high interest in receiving future e‐mail reminders (75%), with the group that received e‐mail reminders more likely to want one in the future than those who did not receive e‐mail reminders (82.5% vs. 69.76%; p = 0.04). Conclusions E‐mail reminders sent after ED visits did not improve patients' adherence to the recommended timing of primary care follow‐up contained in discharge instructions. Subjects in both the control and the intervention groups favorably viewed the concept of e‐mail reminders, suggesting that the value of e‐mail reminders after ED discharge may be in areas such as patient satisfaction that were not specifically targeted for measurement in this study.